Expression of plasminogen activator inhibitor 1 in peritoneal dialysis patients and its regulation of matrix metalloproteinase 2/vascular endothelial growth factor/extracellular regulated protein kinases 1/2 signaling pathway - Liang Xue-yan; Su Rui; Li Ming; Li Ting; Lu Jia-mei; Zou Xiao-rong (Linchuang shenzangbing zazhi)
ObjectiveTo explore the expression and function of plasminogen activator inhibitor 1 （PAI-1） in peritoneal dialysis （PD） patients.MethodsA total of 100 PD patients were selected as research objects. After 7 months of dialysis，they were divided into two groups of high transport and low transport according to the results of peritoneal balance test. At Month 1/7 post-dialysis，the dialysate levels of PAI-1，matrix metalloproteinase-2 （MMP-2） and vascular endothelial growth factor （VEGF） were detected by enzyme-linked immunosorbent assay （ELISA）. C57/BL6 mice were intraperitoneally injected with 3 mL peritoneal dialysate containing 4.25% glucose for 28 consecutive days for establishing a model of peritoneal fibrosis （PF）. The mice were randomly divided into three groups of control，PF+si-NC and PF+si-PAI-1 （n=12 each）. Mice in PF+si-NC and PF+si-PAI-1 groups were intraperitoneally injected with 300 μL negative control siRNA （si-NC） or siRNA targeting PAI-1 （si-PAI-1）. The protein expressions of PAI-1，MMP-2，VEGF，pVEGFR2 and pErk were detected by Western blot. The positive expressions of CD68，VEGF and CD31 were detected by immunohistochemical staining.ResultsAs compared with 1-month dialysis，the dialysate levels of PAI-1，MMP-2 and VEGF became significantly elevated after 7-month dialysis （P<0.05）. As compared with low transport group，the dialysate levels of PAI-1，MMP-2 and VEGF of high transport group were significantly higher （P<0.05）. The area under curve （AUC），sensitivity and specificity of PAI-1，MMP-2 and VEGF in the combined diagnosis of high transport were 0.909，82.61 and 92.45. As compared with PE+si-NC group，extracellular matrix （ECM） deposition and inflammatory cell infiltration declined markedly in PE+si-PAI-1 group. As compared with PE+si-NC group，the positive rates of CD68，VEGF and CD31 were lower in peritoneal tissue of PE+si-PAI-1 group （P<0.05）. As compared with PE+si-NC group，the protein expression levels of PAI-1，MMP-2，VEGF，pVEGFR2 and pErk declined in peritoneal tissues of PE+si-PAI-1 group （P<0.05）.ConclusionThe combined diagnosis of PAI-1，MMP-2 and VEGF offers a high diagnostic value for peritoneal solute transport rate. A down-regulation of PAI-1 may arrest angiogenesis by interfering with MMP-2/VEGF/Erk1/2 signaling pathway，thereby suppressing peritoneal fibrosis.